Multivariate analysis unravels genetic diversity and relationship between agronomic traits, protein, and dietary fiber in yardlong bean (Vigna unguiculata subsp. sesquipedalis Verdc.) - Muhammad Habib Widyawan; Aulia Hasanah; Taryono; Taufan Alam; Rahmi Sri Sayekti; Abrory Agus Cahya Pramana; Rani Agustina Wulandari (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Widyawan MB, Hasanah A, Taryono, Alam T, Sayekti RS, Pramana AAC, Wulandari RA. 2020. Multivariate analysis unravels genetic diversity and relationship between agronomic traits, protein, and dietary fiber in yardlong bean (Vigna unguiculata subsp. sesquipedalis Verdc.). Biodiversitas 21: 5662-5671. Yardlong bean (Vigna unguiculata subsp. sesquipedalis Verdc.) is a vegetable legume that possesses the highest amount of protein and total dietary fiber (TDF) content among other vegetables. However, protein and TDF content diversity are found among yardlong bean genotypes. Genetic improvement to produce cultivars with high yield and improved nutritional content is required. This study aimed to analyze genetic diversity and identify the relationship between important agronomic traits from 21 yardlong bean genotypes assessed by multivariate statistical analysis. The experiment was arranged in alpha design with three replicates, each consist of six blocks. Six pod-related important agronomic traits, protein, and TDF content were observed in this study. Total pod weight, pod weight, and pod length were found to be negatively correlated with protein and TDF content based on correlation and principal component analysis (PCA). Although negatively correlated, several variables possess a large and positive direct effect on protein and TDF content, such as the number of pod, pod weight, and days to flower. D2 analysis and Tocher’s method classify genotypes used in this study into five clusters with diverse traits value. Information from this study laid a foundation for the improvement of important agronomic traits as well as nutritional content in yardlong bean.